Adaptive Neural-Network Boundary Control for a Flexible Manipulator With Input Constraints and Model Uncertainties - Ren, Yong; Zhao, Zhijia; Zhang, Chunliang; Yang, Qinmin; Hong, Keum-Shik (IEEE transactions on cybernetics, 2021)
This article develops an adaptive neural-network (NN) boundary control scheme for a flexible manipulator subject to input constraints, model uncertainties, and external disturbances. First, a radial basis function NN method is utilized to tackle the unknown input saturations, dead zones, and model uncertainties. Then, based on the backstepping approach, two adaptive NN boundary controllers with update laws are employed to stabilize the like-position loop subsystem and like-posture loop subsystem, respectively. With the introduced control laws, the uniform ultimate boundedness of the deflection and angle tracking errors for the flexible manipulator are guaranteed. Finally, the control performance of the developed control technique is examined by a numerical example.